The Relationship between Education Factors, Parents' Occupation and Economic Status on the Incidence of Early Marriage in Young Women in Sigedong Village, Bumijawa District, Tegal Regency - Nur Arifin, Tika; Sri Futriani, Elfira (International Journal of Health and Pharmaceutical (IJHP), 2024)
Background: Marriage is a physical and spiritual bond between a man and a woman as husband and wife with the aim of forming a prosperous familyPurpose of Writing: To find out the relationship between educational factors, parents' occupation and economic status on the incidence of early marriage among young women in Sigedong Village, Bumijawa District, Tega Regency. by researchers in collecting data that is using secondary data. Research Results: There is a relationship between education, occupation, parents' economic status on the incidence of early marriage in young women in Sigedong Village, Bumijawa District, Tegal Regency. Conclusions and Suggestions: It is hoped that the results of this study can be used as a reference for female students about providing health education about early marriage and risks that occur for parents who are too early to marry their children so that they can be applied in community service.